2004
DOI: 10.1007/s11661-004-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain-boundary characteristics on castability of nickel-base superalloys

Abstract: Hot tearing susceptibility of two Ni-base superalloys, IN792 and CM247, during directional solidification was studied. Effects of grain-boundary (GB) misorientation on castability were examined by casting single-crystal (SC) and bicrystal (BC) specimens. Crack-free specimens were obtained in castings with GB misorientation angles of less than ϳ12 deg. Severe cracking occurred if the GB angle was greater than 25 deg. Secondary dendrite arm length right at the GB was found to be larger than in the GB vicinity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 14 publications
4
25
0
Order By: Relevance
“…1 12 It should be emphasized that the material and geometry of the alumina tubes used as molds are exactly the same in the present work as in our earlier work, 12 i.e., the tube-like castings have exactly the same inner and outer diameters as well as wall thickness in both works. The only difference is that the inner alumina is placed at a higher position in the present work, and this change in the test set-up does not influence the level of hot tearing, as will be seen later.…”
Section: A Castability Testsmentioning
confidence: 53%
See 4 more Smart Citations
“…1 12 It should be emphasized that the material and geometry of the alumina tubes used as molds are exactly the same in the present work as in our earlier work, 12 i.e., the tube-like castings have exactly the same inner and outer diameters as well as wall thickness in both works. The only difference is that the inner alumina is placed at a higher position in the present work, and this change in the test set-up does not influence the level of hot tearing, as will be seen later.…”
Section: A Castability Testsmentioning
confidence: 53%
“…SC seeds from superalloy CMSX-4 and PWA1483 were used to initiate the development of CMSX-4 and IN792 SC or BC tube castings, respectively. In our previous work, 12 it was reported that PWA1483 seeds do not influence the nominal composition of IN792 after casting because PWA1483 is the SC equivalent of IN792 having almost the same composition except the minor elements such as B and Zr.…”
Section: A Castability Testsmentioning
confidence: 94%
See 3 more Smart Citations